Fostering Hotel-Employee Creativity Through Micro-Level Corporate Social Responsibility: A Social Identity Theory Perspective - Ahmad, Naveed; Ullah, Zia; AlDhaen, Esra; Han, Heesup; Araya-Castillo, Luis; Ariza-Montes, Antonio (Frontiers in Psychology, 2022)
The present study extended the boundary of social identity theory (SIT) in a collectivistic culture in order to explain the possible association between ML-CSR and EC. Using hotel employees as samples (N=461), a quantitative approach was employed to obtain research objectives. The findings validated the positive relationship between ML-CSR to EC, and WE mediated this relationship. Despite importance of micro-level of corporate social responsibility (ML-CSR) and its link to employee creativity (EC), the underlying mechanism of how and why ML-CSR induces EC remains unclear. Against this backdrop, the current analysis successfully explored the relationship of ML-CSR and EC through the mediating effect of work engagement (WE) in the hotel sector of a developing country. This research is the first study that addresses the criticality of micro-level CSR with the use of social identity theory in the hotel context.